Assessment Conceptions and Practices: Perspectives of Primary School Teachers and Students - Monteiro, Vera; Mata, Lourdes; Santos, Natalie Nóbrega (Frontiers in Education, 2021)
Students’ and teachers’ conceptions about assessment are important because they guide how teachers’ assessments are implemented in the classroom and determine how students study. This multiple-case design study examined (a) how teachers and students view assessment, (b) how teachers assess their students’ learning, and (c) the similarities and disparities that occur when students’ and teachers’ conceptions and teacher practices of assessment are compared. Data were obtained from five third grade classes, involving a total of five teachers and 82 students. Data was gathered through individual interviews with teachers and focus group discussions with students. Moreover, classroom observations and documents produced by the students (worksheets and tests) during math lessons were also analyzed. Results of the content analyses of the data indicated that teachers’ conceptions of assessment are mostly for improvement, while their assessment practices and student conceptions focus on school and student accountability. The results obtained lead us to suggest that student assessment conceptions are constructed from their classroom assessment experiences. The study also suggests that teachers adopt conceptions of assessment inconsistent with their practices that allow them to work within social and contextual constraints.